Institutional influences on women's representation on corporate boards: An Australian case study. Issue 2 (4th February 2014) - Sheridan, Alison; Ross-Smith, Anne; Lord, Linley
Abstract : Purpose: – The purpose of this paper is to interrogate changes to women's representation on boards from an institutional perspective in a particular national context (Australia). Design/methodology/approach: – Drawing on institutional theory at the legal, political and social levels the paper identifies the factors through which women's underrepresentation on corporate boards in Australia gained traction over the period 2009-2012. Findings: – Through the analysis of the Australian context over the period 2009-2012, the paper proposes a framework to represent the multiple, differentiated and often conflicting spheres affecting women's representation on boards and how this may have wider application internationally. Research limitations/implications: – In focusing on the institutional factors, the paper does not mean to underplay organisational factors relevant to women's access to board positions; rather the authors seek to draw attention to how the organisational factors may be shaped by changing institutional "rules". From the interrogation of the conditions under which women's underrepresentation on corporate boards in Australia gained traction, the paper provides a conceptual foundation for the emerging study of institutions and women's representation on corporate boards internationally. Practical implications: – The purpose of documenting these institutional changes in Australia is to be instructive to others addressing the practical problem of how to increase women's representation on boards and what institutional factors may need to be considered to prompt change. Originality/value: – The conceptual framework adds to the as yet relatively under-theorised field of women on corporate boards.